Front Cover: Effects of a Cumulative, Suboptimal Supply of Multiple Trace Elements in Mice: Trace Element Status, Genomic Stability, Inflammation, and Epigenetics. Issue 16 (19th August 2020) - Finke, Hannah; Winkelbeiner, Nicola; Lossow, Kristina; Hertel, Barbara; Wandt, Viktoria K.; Schwarz, Maria; Pohl, Gabriele; Kopp, Johannes F.; Ebert, Franziska; Kipp, Anna P.; Schwerdtle, Tanja
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000325 DOI: 10.1002/mnfr.202000325 The impact of a reduced trace element supply (iron, zinc, copper, iodine, selenium, manganese) on the trace element status, health parameters, epigenetics, and genomic stability is investigated in mice. Reduced trace element supplies distinctly impacted the Fe status. Physical characteristics of the mice are affected and signs of inflammation and increased genomic instability are observed. Global DNA (hydroxy)methylation is unaffected. This is reported by Hannah Finke, Nicola Winkelbeiner, Kristina Lossow, Barbara Hertel, Viktoria K. Wandt, Maria Schwarz, Gabriele Pohl, Johannes F. Kopp, Franziska Ebert, Anna P. Kipp, Tanja Schwerdtle in article 2000325 .